THE INFLUENCE OF BRAND IMAGE, PRICE PERCEPTIONS AND PROMOTIONS ON CONSUMERS' PURCHASE INTEREST IN BEAUTY PRODUCTS IN THE SOCIOLLA APPLICATION - Deva Safrina; Suadi Sapta Putra; kumba.digdo@civitas.unas.ac.id (SEAN Institute, 2023)
The research aims to analyze the influence of brand image, price perception, and promotion on consumer buying interest in beauty products on the Sociolla application. The research source uses primary data, namely questionnaires, this research data was given to 87 respondents. This research uses a purposive sampling method. The data analysis technique used is multiple linear regression and hypothesis testing using t-statistics processed in SPSS 23. The results show that brand image has an effect but not significant on buying interest, price perception has an effect but not significant on buying interest, and promotion has a positive effect and significant to buying interest.